“Go and Look in the Mirror and Make a Change, Mum”: Motherhood and Identity Change in Women’s Desistance in New Zealand - Low, Grace (Women & criminal justice, 2023)
This article is derived from the first New Zealand-based study to examine in detail the potential role of motherhood in women’s desistance. Narrative interviews were carried out with 13 mothers, predominantly Māori,1 with histories of incarceration. For one woman, becoming a mother for the first time was a clear turning point in her desistance. For most of the women, motherhood did not function as an initial turning point but was instrumental in facilitating desistance later in life. The article illuminates some of the socio-structural factors which can limit the potential for motherhood to positively influence the desistance process. It also examines the internal mechanisms by which motherhood inspired or cemented the women’s later desistance with a specific focus on the change-driving effects of critical self-reflection. Finally, this article suggests that, for mothers, the journey toward tertiary (relational) desistance requires their children to accept, or at least recognize, their changed identities.